Characterizing the role of the MRTF-ASRF pathway in shear induced cytoskeletal remodeling - Maksoud, Fatima (University of Ottawa (Canada), 2009)
Laminar shear stress is atheroprotective mainly due to its effect on endothelial cell morphology. Endothelial cells subjected to laminar flow elongate, align in the direction of flow and form robust stress fibers which align along with microtubules parallel to the direction of flow. We investigated the role of the actin/MRTF-A/SRF pathway in mediating the endothelial remodeling response. We hypothesize that MRTF-A is required for shear induced cytoskeletal remodeling to occur. We were able to show that MRTF-A translocates to the nucleus within 3 hours of shear stress application. The duration of nuclear translocation was short term lasting only 6 hours. After 6 hours of flow, MRTF-A was predominantly cytoplasmic. The inhibition of ROCK abolished shear induced MRTF-A nuclear translocation and cytoskeletal remodeling. The inhibition of PI-3 kinase, myosin II and GSK-3beta attenuated shear induced MRTF-A nuclear translocation and cytoskeletal remodeling whereas the inhibition of Rac1 and MEK had no effect. Shear induced MRTF-A nuclear translocation and the cytoskeletal remodeling response appear to be largely ROCK dependent. In addition, we investigated the requirement of MRTF-A for cell migration. HUVECs infected with adenovirus expressing a dominant negative form of MRTF-A were unable to migrate in a scratch wound assay. Moreover, HUVECs expressing DN MRTF-A were unable to form a capillary network consisting of dispersed cells in a matrigel assay but formed networks where cells remained in clumps.
Keywords: Biology, Molecular.